2017
DOI: 10.5588/ijtld.16.0939
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance patterns among extra-pulmonary tuberculosis cases in a tertiary care centre in North India

Abstract: The burden of drug resistance, including M/XDR-TB, among EPTB patients is high. Novel molecular tests can help in early diagnosis and treatment to prevent disease progression and amplification of resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 0 publications
5
16
0
Order By: Relevance
“…Moreover, high MDR-TB in our study might be due to the difference in the study setting where the current study is conducted in an urban setting. However, our findings were consistent with previous studies [26,28,30,37,38].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Moreover, high MDR-TB in our study might be due to the difference in the study setting where the current study is conducted in an urban setting. However, our findings were consistent with previous studies [26,28,30,37,38].…”
Section: Discussionsupporting
confidence: 94%
“…In this study, INH mono-resistance was 3 (2%) which is relatively similar to the earlier study reported from Ethiopia [29] and India [27]. Another study reported from North India [30] indicated a higher proportion of INH mono-resistance than our result. This difference could be due to variation in treatment adherence, mutations, early introduction of drugs in the country, and high dose INH use for MDR treatment.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In last decade, the use of several molecular diagnostic techniques like Xpert MTB/RIF and LPA have increased the DR-TB case notification rate worldwide 12 . RIF-resistant (RR) associated rpoB gene hotspot (codon 507-533) is identified as the principle RR-TB defining region in all the nucleic acid amplification tests based molecular diagnostics 13 .…”
Section: Discussionmentioning
confidence: 99%
“…It should be differentiated from other common respiratory diseases such as tuberculosis which contributes to over one-quarter (27.3%) of the global TB burden in India alone. (Sharma et al, 2017), (Sharma et al, 2018). It shows symptoms like cough with expectoration, weight loss, fatigue, night sweats and evening rise in temperature.…”
Section: Figure 1: Renin Angiotensin System (Ras)mentioning
confidence: 99%